Emotional Perception And Ergonomic Design Innovation Of A Portable Chicken Feather Cleaner: A Kansei Engineering Study - Iswanto; Puta, Boy Isma; Fauzan, Muhammad; Setiawan, Hendri; Jakaria, Ribangun Bamban; Yakoob@Ariffin, Nur Haizal Binti Mat Yakoob@Ariffin (Journal of Research and Technology, 2025)
Users' emotional perception plays a crucial role in the development of effective ergonomic product designs, particularly in tools used for domestic and small-scale industrial activities. This study aims to investigate the influence of emotional perception on the ergonomic design innovation of a portable chicken feather cleaning tool using the Kansei Engineering approach. This method was employed to translate user emotions and perceptions into measurable and implementable design elements. The research process involved identifying relevant kansei words, collecting perception data from 60 respondents using a semantic differential scale questionnaire, and performing factor analysis and Principal Component Analysis (PCA) to determine the core affective dimensions. The results revealed that physical comfort, form perception, and motion efficiency are the dominant factors influencing user preferences. Based on these findings, an ergonomic prototype was developed by optimizing hand posture, device weight, and handle shape. The study concludes that integrating emotional dimensions into the design process significantly enhances product-user affective compatibility, potentially improving both work efficiency and user satisfaction. These findings offer practical implications for the design of functional household tools based on human-centered design principles.